2003
DOI: 10.1111/1468-2508.t01-3-00014
|View full text |Cite
|
Sign up to set email alerts
|

A New Approach for Testing Budgetary Incrementalism

Abstract: We present evidence suggesting that the widely used regression method for testing budgetary incrementalism (Davis, Dempster, and Wildavsky, 1966a, 1966b, 1971 is not suited for U.S. budgetary data that appear to be nonstationary. The method, moreover, cannot detect a nonincremental period following (or preceding) an incremental period. We offer an alternative method that is valid even in nonstationary cases. Our method exploits both the crosssectional and time-series characteristics of the budgetary data to id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
39
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 49 publications
3
39
0
1
Order By: Relevance
“…The literature shows that budget figures usually follow the incremental approach (see Dezhbakhsh et al. ). This means that as far as budgets are concerned, a particular year t figure depends to some extent on year t‐1 figure.…”
Section: Methodsmentioning
confidence: 99%
“…The literature shows that budget figures usually follow the incremental approach (see Dezhbakhsh et al. ). This means that as far as budgets are concerned, a particular year t figure depends to some extent on year t‐1 figure.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, another study in this area of budgetary practices and outcomes examined federal budgetary appropriations to 103 agencies between 1946 and 1996. Dezhbakhsh et al (2003) found that overall, incremental budgeting was the predominant pattern of decisionmaking observed. Only minor departures from this pattern occurred during presidential election years, and when Democrats controlled both houses in Congress (Dezhbakhsh et al, 2003).…”
Section: The Incremental Approachmentioning
confidence: 98%
“…The decision of "who gets what" is based primarily on the previous year's allocation. In most cases, each agency is allocated a similar increase or decrease in their departmental budgets, and the actual agency share of municipal budget remains highly stable over time (Bailey & O'Connor, 1975;Bozeman & Straussman, 1982;Dezhbakhsh, Tohamy, & Aranson, 2003;Lewis, 1984).…”
Section: The Incremental Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…Rios, Pascual, and Cabases (2017, in this issue) extend traditional spatial spillover models, applied to government spending policies in Spain, by including dynamic effects and endogenous and exogenous interaction effects. The justification for dynamic effects are closely linked the incremental budgetary assumption (Davis, Dempster, & Wildavsky, 1966;Dempster & Wildavsky, 1979;Simon, 1995;Dezhbakhsh, Tohamy, & Aranson, 2003). Accordingly, the paper compares not only own and neighbouring levels of expenditure but also past and future expenditures over time.…”
Section: Palabras Clavesmentioning
confidence: 99%